Peran Pembiayaan Mikro Syariah dalam Pengembangan Perdagangan di Kehidupan Masyarakat - Ulandari, Anisa; Rizkiyah, Azimaya; Uswatun, Try; Ramadani, Balqis; Efri Yuni, Dera (Journal of Economics and Business, 2024)
ABSTRACT  Islamic microfinance is one of the important instruments in encouraging the growth of trade in the community. Based on fair and transparent sharia principles, Islamic microfinance offers financial solutions for micro and small businesses that are constrained by access to capital. Islamic microfinance has become one of the important instruments in the development of commerce in people's lives. Based on fair and transparent sharia principles, Islamic microfinance offers alternative solutions for small and medium enterprises that are often constrained by access to capital. This journal will examine the role of Islamic microfinance in the development of trade in various aspects of people's lives. It starts with the definition and basic principles of Islamic microfinance, then discusses its benefits for MSMEs and the wider community. Furthermore, this journal will examine the various Islamic microfinance products and schemes available, as well as the challenges and opportunities for its development in the future. ABSTRAK Pembiayaan mikro syariah merupakan salah satu instrumen penting dalam mendorong pertumbuhan perdagangan di kehidupan masyarakat. Berdasarkan prinsip syariah yang adil dan transparan, pembiayaan mikro syariah menawarkan solusi keuangan bagi para pelaku usaha mikro dan kecil yang terkendala akses modal. Pembiayaan mikro syariah telah menjadi salah satu instrumen penting dalam pengembangan perdagangan di kehidupan masyarakat. Berdasarkan prinsip syariah yang adil dan transparan, pembiayaan mikro syariah menawarkan solusi alternatif bagi para pelaku usaha kecil dan menengah (UMKM) yang seringkali terkendala akses permodalan. Jurnal ini akan mengkaji peran pembiayaan mikro syariah dalam pengembangan perdagangan di berbagai aspek kehidupan masyarakat. Dimulai dengan definisi dan prinsip dasar pembiayaan mikro syariah, kemudian membahas manfaatnya bagi UMKM dan masyarakat luas. Selanjutnya, jurnal ini akan menelaah berbagai produk dan skema pembiayaan mikro syariah yang tersedia, serta tantangan dan peluang pengembangannya di masa depan.